Assessment of engine operability and overall performance for parallel hybrid electric propulsion systems for a single-aisle aircraft - Kang, Sangkeun; Roumeliotis, Ioannis; Zhang, Jinning; Broca, Olivier; Pachidis, Vassilios (American Society of Mechanical Engineers (ASME), 2022)
This paper aims to assess the gas turbine operability and overall hybrid electric propulsion system (HEPS) performance for a parallel configuration applied to a 150 passenger single-aisle aircraft. Two arrangements are considered: one where the low-pressure (LP) shaft is boosted and one where the high-pressure (HP) shaft is boosted. For identifying limits in the hybridization strategy, steady-state and transient operation are considered, and the hybridization effect on compressor operability is determined. Having established the electric power on-take limits with respect to gas turbine operation, the systems performance at aircraft level is quantified for the relevant cases. Different power management strategies (PMS) are applied for the two arrangements and for different power degrees of hybridization. The results indicate that despite the fact that pollutant emission and fuel consumption may improve for hybrid propulsion, this comes at the cost of reduced payload and operability margins. Boosting the LP shaft may give the highest engine performance benefits but with a significant weight penalty, while the LP compressor system operability is negatively affected. On the other hand, boosting the HP shaft provides lower engine performance benefits but with smaller weight penalty and with less operability concerns.
Keywords: Aircraft; Electric propulsion; Electricity (Physics); Engines; Gas turbines; Weight (Mass); Trains; Emissions; Transients (Dynamics); Steady state; Fuels; Flow (Dynamics)